2005
DOI: 10.2478/bf02476237
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of some aromatic copolyethers containing a propylenic spacer

Abstract: Abstract:The main objective of this paper is to study the thermal stability of some aromatic copolyethers containing a propylenic spacer. Some of the investigated copolyethers displayed a liquid crystalline (LC) behavior, with the presence of the mesogenic groups in the main chain, inducing high values of the thermal transition temperatures. As a consequence, a thermal stability study was necessary to establish the maximum temperature value for the LC behavior characterization. A thermal degradation mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Figure 4 presents ionic current variation versus temperature for a few ionic fragments identified in the mass spectra. Previous results obtained in our laboratory on different classes of polymers containing azo groups in the main chain, 27,28 or those presented by other researchers 29,30 suggest that the thermal degradation process begins with scission in the –N=N– groups. However, the m / z = 28 signal was not evident in our mass spectra.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Figure 4 presents ionic current variation versus temperature for a few ionic fragments identified in the mass spectra. Previous results obtained in our laboratory on different classes of polymers containing azo groups in the main chain, 27,28 or those presented by other researchers 29,30 suggest that the thermal degradation process begins with scission in the –N=N– groups. However, the m / z = 28 signal was not evident in our mass spectra.…”
Section: Resultsmentioning
confidence: 57%
“…In order to elucidate certain aspects of the degradation mechanism of samples 1 and sample 2, the study was continued using a TG-MS-FTIR technique: a thermogravimetric analyses model STA 449F1 Jupiter (Netzsch, Germany), coupled with spectrophotometer FTIR model Vertex-70 (Bruker, Germany) and a mass spectrometer model QMS 403C Aëolos (Netzsch, Germany). Since some previous studies developed within the group 27,28 showed that the azo-benzenic segment is the link that triggers the polymer degradation process, most of the attention was given to this segment. The recorded mass and FTIR spectra enabled the identification of ionic fragments occurring within the temperature range 25–600 °C, that explain some aspects of the –N=N– group scission.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported for other azopolymers as well. 32,33 The thermal degradation was also found to remain the same despite the increase in the degradation rate, as the DTG curves had the same appearance. At a rate of heating of 16 C min À1 and within the 400-700 C temperature range, the only exception was the polymer Ic whose degradation processes were different from the ones achieved at lower degradation rates (Figure 3).…”
Section: Thermal Stability Of Polymersmentioning
confidence: 69%
“…This behavior was determined by the presence of the azo groups, which represent the weakest link from the viewpoint of their thermal stability. Previous studies have shown that the azobenzene groups began to degrade when nitrogen molecules were removed from the system [17]. The influence of the heating speed did not alter the thermal characteristics significantly.…”
Section: Heating Speed Stagementioning
confidence: 75%